Filtering antennas for energy harvesting in wearable systems. (25th July 2019) - Dong, Yazhou; Gao, Steven; Luo, Qi; Dong, Shi‐wei; Wei, Gao
Abstract: Wearable systems are important for future smart home care for the disabled and ageing population. One of the key challenges is the power supply. One solution is to develop an energy harvesting system suitable for providing power wirelessly. The matching network and filter in traditional energy harvesting system occupy lots of space, introduce additional losses, and reduce the total efficiency. This paper presents a novel filtering antenna suitable for wearable energy harvesting systems. The developed antenna has a broadband operation, harmonics suppression, compact size, and low cost. Firstly, a novel technique for broadband filtering antenna modeling and design in order to realize complex input impedance is presented. By adjusting the external quality factors and coupling coefficients of the resonators, complex impedance matching can be realized. Then, the theory of characteristic mode is used for the modal analysis of the filtering antenna. To verify the design concept, a C‐band circularly polarized filtering antenna with complex impedance is designed and fabricated. The results show that the impedance bandwidth is more than 14.5% with a peak gain higher than 8.5 dBi. The proposed antenna is conjugate matched to the rectifying circuit at 5.8 GHz and mismatched at the second harmonic frequency to suppress the harmonic reradiation, leading to a compact rectenna structure.